Comprehensive study of pydiflumetofen in Danio rerio: Enantioselective insight into the toxic mechanism and fate. (September 2022) - Wang, Zhen; Tan, Yuting; Li, Yanhong; Duan, Jinsheng; Wu, Qiqi; Li, Rui; Shi, Haiyan; Wang, Minghua
Graphical abstract: Highlights: The toxic effects of R -PYD against zebrafish was higher than S -enantiomer. Stronger binding of R with SDH causing lower enzyme activity led to higher toxicity. Enantioselectivity of uptake, distribution and metabolism of PYD was observed. The phase I and phase II metabolic pathways of PYD in zebrafish were first proposed. Several highly toxic metabolites need to be given more attention in the future. Abstract: Pydiflumetofen (PYD) is primarily used to control fungal disease. The potential risks posed by PYD enantiomers to the aquatic ecosystem are currently unclear. In this study, the enantioselective toxicity and fate of PYD in Danio rerio were investigated, and the enantioselective toxic mechanism and metabolic pathway were explored. The acute toxicity of R -PYD was 10.7–14.7-fold than that of S -PYD against Danio rerio embryos, larvae, and adults. Meanwhile, R -PYD presented a stronger effect on embryo hatching and abnormalities, adult tissue damage and oxidative stress. R -PYD inhibited the succinate dehydrogenase (SDH) activity more than S -PYD because of its better interaction with SDH with a lower binding free energy (-59.35 kcal/mol), explaining the mechanism of enantioselective toxicity. Remarkable enantioselectivity was observed in uptake, distribution, and elimination. R -PYD showed preferential uptake with the higher uptake rate constants and slow metabolism with a longer half-life, resulting in the bioaccumulation of R -PYD with higher BCFk (7.37 at 0.05 mg/L and 14.69 at 0.2 mg/L). Besides, muscle is an important tissue for PYD accumulation, existing potential food risk. Eleven PYD metabolites were qualitatively identified, and the metabolic pathway was proposed, including hydroxylation, N -demethylation, demethoxylation, hydrolysation (phase Ⅰ), and acetylation and glucuronidation (phase Ⅱ). The predicted toxicity of the metabolite indicated that several highly toxic metabolites need to be considered in the future. This study provides a new perspective for evaluating the ecological and human health risks of chiral pesticides.